Improved Robust Control of a New Morphing Quadrotor UAV Subject to Aerial Configuration Change - Derrouaoui, Saddam Hocine; Bouzid, Yasser; Belmouhoub, Amina; Guiatni, Mohamed (Unmanned systems (Singapore), 2025)
Over these last years, morphing Unmanned Aerial Vehicles (UAVs) control became one of the critical problems, which has not been properly solved by the researchers. This is due to their particular and complex features compared to the ordinary ones as: morphology change, flight transition, model asymmetry, geometric variation, different dynamics, over-actuation and high nonlinearity. To deal with such challenges, this paper addresses the control of a new over-actuated morphing drone that changes its arms in different orientations to form various morphology and configuration models. First, the present system is divided into two principal parts: an attitude subsystem and a position subsystem. Furthermore, an improved Adaptive Nonsingular Fast Terminal Sliding Mode Controller (ANFTSMC) is proposed to stabilize the attitude loop. While the position loop is controlled by Integral Backstepping Controller (IBC) using Lyapunov theory. Second, with the aim to better adjust the control gains, a recent metaheuristic technique based on the Whale Optimization Algorithm (WOA) is adopted. At last, a comparative study with the standard control algorithms is accomplished to evaluate the effectiveness and robustness of the proposed methods.